Evaluation of the physical activity level, nutrition quality, and depression in patients with metabolic syndrome: Comparative study (vol 97, e10485, 2018) - Kazaz, Ismet; Angin, Ender; Kabaran, Seray; Iyigun, Gozde; Kirmizigil, Berkiye; Malkoc, Mehtap (Lippincott Williams & Wilkins, 2018)
[Abstract Not Available]